Analisis Yuridis Relevansi Ekowisata Bagi Pembangunan Ekonomi Dan Konservasi Alam - Sabowo, Hudi Karno; Purwanto, Purwanto; Saryana, Saryana (PMIH Untag Semarang, 2024)
Ecotourism is the empowerment of a sustainable tourism sector by utilizing the gifts of ecosystems and the existence of culture in natural habitats. Taking advantage of biodiversity. by paying attention to the concept of nature conservation and the surrounding environment. Ecotourism, as part of the tourism sector, is a leading sector globally which is used as a source of the nation's and state's economy which continues to be developed and needs to be improved. Considering the socio-economic aspect, the tourism sector is proven to be able to contribute to increasing income starting at the community level, opening and expanding employment opportunities, to increasing income for the government and increasing the country's foreign exchange, because through the tourism sector it has grown new businesses by encouraging regional economic development in the form of various kinds of entrepreneurship in the surrounding community. The research method carried out in scientific writing here uses normative juridical methods. Namely legal research through library study by examining predetermined library materials or sources accompanied by other secondary data, with an emphasis on problems related to the research topic. The research concluded that the concept of ecotourism development cannot be separated from the connection or relevance of local governments in managing and utilizing local communities. As stated in the regional autonomy policy. The obstacles are the lack of management and the lack of supporting capacity of the local community. Therefore, the successful use and management of ecotourism destinations is a collective responsibility, not only the burden of the government, but also local communities and managers. So that all these lines communicate with each other, facilitated by the regional or central government. Furthermore, it provides information on the importance of preserving natural resources, including the existence of diverse biodiversity, flora and fauna. So that the natural principles inherent in ecotourism can be sustainable and develop well.